AI AS “UNSTOPPABLE” AND OTHER INEVITABILITY NARRATIVES IN TECH: ON THE ENTANGLEMENT OF INDUSTRY, IDEOLOGY, AND OUR COLLECTIVE FUTURES - Tacheva, Zhasmina; Appedu, Sarah; Wright, Mirakle (AoIR Selected Papers of Internet Research, 2025)
The world today is awash with narratives of artificial intelligence (AI) as an "inevitable," "unstoppable" force destined to "revolutionize" society. Using the concept of "entanglement" from Black and Indigenous feminist science, technology, and society studies, we provide a critical examination of the AI industry's complex intersections with sociopolitical dynamics, technological determinism, and oppression. Instead of viewing AI advancement as a predetermined path, we show how this perspective is socially constructed and has dire consequences for the environment and society alike, especially for marginalized communities in the global and local Souths.Using discourse analysis and critical quantitative techniques, we analyze the discourses surrounding AI, examining over 1,200 pieces of digital content to show how language shapes both technology's development and our collective imaginations. By tracing the ideological roots of AI back to colonial and eugenic practices, we demonstrate the industry's deep entanglement with interlocking systems of oppressions.